KEBIJAKAN LUAR NEGERI KANADA KELUAR DARI PROTOKOL KYOTO TAHUN 2011 - Bahjatul Murtasidin (Jurnal Kebijakan Publik, 2016)
Foreign Policy Out Canadian of the Kyoto Protocol in 2011. This research aims toexplain factors of Canada withdrawal policy toward Kyoto Protocol in 2011 under Stephen Harper.This research uses Foreign Policy Theories by James N. Rossenau, and applies qualitative researchmethod. The Research shaw that Canada withdrawal policy toward Kyoto Protocol in 2011 isaffected by five factor. First, Harper’s views on Kyoto Protocol. Second, the ideology ofconservative party which was the winning and most dominated party in Canada’s parliament.Third, the dynamics of Canada’s federal government and provincial government relations thathas some problem in jurisprudence matters. Forth, overall domestics condition of Canada’senvironment and its national interests. And the final factor, international systems which showssome inconsistencies of big power states on Kyoto Protocol. The most dominant factor is Harper’sviews on Kyoto Protocol and the ideology of conservative party.